2022
DOI: 10.3390/bdcc6010031
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Citizens’ Intention to Use Open Government Data—A Case Study of Pakistan

Abstract: Open government data (OGD) has gained much attention worldwide; however, there is still an increasing demand for exploring research from the perspective of its adoption and diffusion. Policymakers expect that OGD will be used on a large scale by the public, which will result in a range of benefits, such as: faith and trust in governments, innovation and development, and participatory governance. However, not much is known about which factors influence the citizens’ intention to use OGD. Therefore, this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The second factor “Intention to Adopt OGD Portals” accounts for 11.353 % of total variance and is defined by six statements (Cronbach’s alpha = 0.831). For the following six items, we used statements from questionnaires used in similar studies by Shiau et al (2018, p. 10) and Khurshid (2022, p. 18), after revising them to suit the present study: {Q:ADOPT4} I support adopting OGD. {Q:ADOPT5} I look forward to using OGD to meet the needs of work or life. {Q:ADOPT6} I highly recommend using OGD to others. {Q:ADOPT3} I feel good about adopting OGD. {Q:ADOPT2} I believe it is a good idea to adopt OGD. {Q:ADOPT1} I plan to make more use of OGD in the future. …”
Section: Procedures and Methodologymentioning
confidence: 99%
“…The second factor “Intention to Adopt OGD Portals” accounts for 11.353 % of total variance and is defined by six statements (Cronbach’s alpha = 0.831). For the following six items, we used statements from questionnaires used in similar studies by Shiau et al (2018, p. 10) and Khurshid (2022, p. 18), after revising them to suit the present study: {Q:ADOPT4} I support adopting OGD. {Q:ADOPT5} I look forward to using OGD to meet the needs of work or life. {Q:ADOPT6} I highly recommend using OGD to others. {Q:ADOPT3} I feel good about adopting OGD. {Q:ADOPT2} I believe it is a good idea to adopt OGD. {Q:ADOPT1} I plan to make more use of OGD in the future. …”
Section: Procedures and Methodologymentioning
confidence: 99%
“…It may improve user willingness towards continuous interaction with the data retrieval system, motivating them to discover more required data. Studies related to the design of data retrieval systems paid more attention to usability, ease of use (Koesten et al, 2017;Wu et al, 2019) and users' perceived enjoyment (Khurshid et al, 2022). By discussing the negative impact of achievement value on search effort and the intention to access data, this paper provides new insights for developers to delay users' satisfaction and maintain their willingness to explore data.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Voluntariness of use (VU) is defined in terms of the extent to which an individual engages with OGD of her/his own volition (Lnenicka et al, 2022). Whilst voluntary engagement with OGD has been clinched in some contexts, it was found inconsequential in others (Khurshid et al, 2022;Purwanto et al, 2020b;Saxena and Janssen, 2017). It is hypothesized that: H5.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Extant OGD-hinged research has shown mixed findings vis-a-vis the aforesaid quality dimensions (Khurshid et al, 2022;Lnenicka et al, 2022). It is hypothesized that:…”
Section: Research Model and Hypothesesmentioning
confidence: 99%